Design and Implementation of a Pharmaceutical Inventory Database Management System - Samaan, Sama Salam (Al-Khwarizmi Engineering Journal, 2017)
The main aim of this paper are the design and implementation of a pharmaceutical inventory database management system. The system was implemented by creating a database containing information about the stored medicines in the inventory, customers making transactions with the pharmaceutical trading company (which owns the inventory), medical suppliers, employees, payments, etc. The database was connected to the main application using C sharp. The proposed system should help in manag inginventory operations which include adding/updating employees’ information, preparing sale and purchase invoices, generating reports, adding/updating customers and suppliers, tracking customer payments and checking expired medicines in order to be disposed. The system can be used to facilitate smooth workflow of sale and purchase operations and bring the advantages of having the most efficient control with minimal efforts.